Use of a Lewis acid, a Brønsted acid, and their binary mixtures for the hydrothermal liquefaction of lignocellulose. (15th November 2021) - Alper, Koray; Wang, Yun-Yan; Meng, Xianzhi; Tekin, Kubilay; Karagoz, Selhan; Ragauskas, Arthur J.
Graphic abstract: Highlights: Hydrothermal liquefication of teak wood biomass to produce bio-oils. Optimization of the hydrothermal liquefication conditions. Utilization of a Lewis acid, a Brønsted acid and their mixture at different molar ratios. The impact of catalyst type and amount on the yield and compositions of the bio-oils. Abstract: The main objective of the present study is to investigate the effect of a Lewis acid, Brønsted acid, and their combined use on the hydrothermal liquefaction of lignocellulosic biomass. Hydrothermal liquefaction of teak wood was conducted at 250, 300 and 350 °C for 15, 30 and 60 min. Hydrothermal liquefaction of teak wood was carried out at 300 °C for 30 min (the best optimum conditions) without and with the use of Mg(ClO4 )2, HClO4, and HClO4 /Mg(ClO4 )2 at various loadings (2–10 mmol/15 g wood). The highest bio-oil yield was obtained with the non-catalytic run. All tested catalysts have negative effect on bio-oil yields. The bio-oil yields generally decreased with increasing the catalyst loadings. The deoxygenation degree in bio-oils changed depending on the type of catalyst and loading. A high degree of de-oxygenation took place with Mg(ClO4 )2 catalysts. An increased catalyst loading led to decreased aromatic contents of bio-oils catalysed by either Mg(ClO4 )2 or HClO4 . The use of a catalyst increased total naphtha fractions in bio-oils. The highest heating value of the bio-oil was estimated to be approximately 30 MJ/kg. Gas chromatography–mass spectrometry analysis revealed that the bio-oils from the non-catalytic and catalytic runs contained aldehydes, ketones, phenols, acids, esters and alcohols. The relative yields of the oxygenated compounds were affected by catalyst type.